The informational value of insurance purchases: Evidence from the property-liability insurance market - Ligon, James A.; Cather, David A. (Journal of Banking & Finance, 1997)
The purchase of insurance provides a potentially finer informational partition over the distribution of post-loss resolution wealth that may allow favorable adaptation of intermediate consumption, investment, or other decisions. Such a positive informational value does not require consumer risk aversion. Lines of insurance with longer resolution periods should impact relatively more decisions and have higher informational value. Under standard assumptions on preferences, in the absence of informational value, risk premiums paid for insurance by risk averse consumers should not increase as the loss resolution period increases. Empirical tests using data from the property-liability insurance market suggest that the willingness to pay per dollar of coverage (as measured by relative market demand across lines of insurance) is greater for lines of insurance with longer resolution periods consistent with a positive informational value of insurance. The results suggest that other financial assets may also have differential informational value.